RANCANG BANGUN APLIKASI KINERJA PENELITIAN DAN PENGABDIAN MASYARAKAT DOSEN ILMU KOMPUTER UNIVERSITAS BANTEN JAYA BERBASIS WEB - Widyawati Widyawati; Ahmad Fatoni; Dimas Sudarwanto (Journal of Innovation And Future Technology (IFTECH), 2020)
According to Law article. 20 of 2003 concerning the National Education System, Article 20 clearly states that universities are obliged carry out research and community service, in addition carry out education. Faculty of Computer Science, University of Banten Jaya at processes ranging from administration and in research and data management this community service still uses the manual method so that when LPPM institutions want to monitor research and community service activities experience difficulty. For that, it is necessary to have an application that can facilitate institutions and faculties in monitoring research activities and community dedication. This study uses the Waterfall design method, while the method data collection used is by observation interviews and studies References. Tools used in designing this system using modeling Unified Modeling Language. Applications tested using black box method. The results of testing this application conclude that the function which is expected everything in accordance with the wishes.